Аналіз атмосферного загасання каналу Free Space Optical - Рязанов, С. С.; Токар, Л. О. (ХНУРЕ, 2025)
The paper reviews free space optical communication systems (FSO), shows their advantages and limitations. The dependence of the channel on weather conditions is analyzed and significant attenuation of the optical signal is revealed. The study was conducted by calculating all components of atmospheric attenuation and by modeling the FSO channel in the Mathlab environment. The distance between the transmitter and the receiver, typical wavelengths used in fiber optics, and standard characteristics of the FSO channel were used as the initial parameters.
Keywords: Free Space Optical; атмосферне загасання каналу